THE ROLE OF RESTORATION AND SCIENTISTS IN THE PRESERVATION OF ARCHITECTURAL MONUMENTS OF THE TEMURID PERIOD - Makhmudova, Malika; Makhmudova, Mukhayyo (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article introduces the history of researches and study of the restoration of architectural monuments of the Temurid period. The architecture of the Temurid period of the Central Asian countries and Afghanistan, covering the period from the 14thto the 15thcenturies, is one of the brightest phenomena of world architecture. Amir Temur was one of the few leaders who was not only the creator of outstanding architectural masterpieces, but was also able to form a special architectural style in his state. The gardening art of this period also reached a high development. Therefore, the study and research of the architecture of this period, as well as its restoration is an extremely important task in world architecture. In this regard, the scientific, research, restoration works of many famous scientists, architects, architects-restorers are of great importance. Among them are Mauer, Zasypkin, Pugachenkova, Mankovskaya, Notkin, Zakhidov, Kryukov, Filimonov and many others who made invaluable contribution to the formation of and the development of the restoration school of Uzbekistan, as well as in the promotion and preservation of the cultural heritage of the Temurid period both in Uzbekistan and abroad. The experience of methods of restoration and conservation of architectural monuments of the Temurid period, including their architectural, compositional and artistic solution is considered and studied in the article.